Contrasting bleaching severity between marine protected and coral restoration areas on Pramuka Island, Indonesia - ZULFANDRA BACHRUL KALAM; ALFAIZ ARSELAN; DENNY KHAERUDI; DONDY ARAFAT; NEVIATY P. ZAMANI; NYOMAN METTA N. NATIH; RADIXA RADYA RAMADHAN HARYANTO; INNA PUSPA; SYAMSUL BAHRI AGUS; BEGINER SUBHAN (Society for Indonesian Biodiversity, 2026)
Abstract. Kalam ZB, Arselan A, Khaerudi D, Arafat D, Zamani NP, Natih NMN, Haryanto RRR, Puspa I, Agus SB, Subhan B. 2026. Contrasting bleaching severity between marine protected and coral restoration areas on Pramuka Island, Indonesia. Biodiversitas 27 (5): d270531. https://doi.org/10.13057/biodiv/d270531. The 2023-2024 global coral bleaching event provided an urgent context for assessing reef responses under contrasting management regimes. This study compared bleaching prevalence, hard coral cover, genus composition, and life-history strategy distributions between a Marine Protected Area (MPA) and an active coral restoration site (RPTRA Smiling Coral) on Pramuka Island, Thousand Islands, Indonesia. Surveys were conducted in January 2024 using a rapid photo-quadrat method across three depth strata (5, 10, and 15 m) at both sites. The MPA exhibited severely degraded coral cover (below 25% at all depths) and extremely high bleaching prevalence (83.75-91.81%), with near-total bleaching in dominant genera including Pachyseris spp. and Pleuractis spp. In contrast, the RPTRA restoration site showed bleaching rates below 33% across all depths, with Porites spp. displaying more stable responses. Despite uniform water temperatures of 30°C across all depths, bleaching was most severe at 5 m, suggesting that light intensity amplifies thermal stress in shallow habitats. Critically, all four life-history strategies were represented among bleached genera, indicating that even stress-tolerant corals are approaching their thermal tolerance limits. These findings indicate that sites under active restoration were associated with substantially lower bleaching prevalence and better ecological condition than the passively protected MPA, consistent with the hypothesis that active restoration enhances post-bleaching recovery capacity. This association has implications for the long-term biodiversity resilience of coral communities under escalating climate stress, though the observational design precludes direct causal attribution.